EFFECT OF INSTITUTIONALIZATION ON BEHAVIOURAL ADJUSTMENTS OF INSTITUTIONALIZED SCHOOL GOING CHILDREN - NASREEN BANU, N. SANDHYA RANI, M.SARADA DEVI and (The Journal of Research, PJTSAU, 2017)
Institutional care is defined as â€œa group living arrangement for more than ten children, without parents or surrogate parents, in which care is providedby a much smaller number of paid adult carersâ€. In such a type of alternative care the guardianship of the children resides with the institution and there are individuals hired to act as caretakers of the children residing in the institution (Brown 2009). Institutional care is increasing in countries where there is economic transition, because for many families andcommunities the changes have increased unemployment, migration for work, family breakdown and single parenthood (Carter, 2005; Tinova et al.,2007).Children living in substandard orphanages have been reported to display a variety of other atypical behaviours, including stereotyped self-stimulation, a shift from early passivity to later aggressive behaviour, over-activity and distractibility, inability to form deep or genuine attachments, indiscriminate friendliness, and difficulty establishing appropriate peer relationships (Vorria et al.,1998).